Challenges of Professional Forestry Education - A Thought - Lahiri, A. K. (Indian Forester, 2013)
Gradually holistic management of forests being aimed to obtain tangible and intangible benefits the forest communities and other stakeholders are being involved for sustainable management of forests. Already the process has been initiated but there are successes and failures and there is need for research inputs. So suggestion has been made to include certain subjects/topics in the curriculum and also need to carryout researches to provide appropriate inputs for training by the various universities, institutes carrying researches and running academic courses and also input from the success stories and best practices from the field to carry out the challenging task of conservation.